The day the residents left: lessons learnt from COVID-19 for ambulatory clinics. Issue 3 (31st July 2020) - Doolittle, Benjamin R; Richards, Bradley; Tarabar, Amerisa; Ellman, Matthew; Tobin, Daniel
Abstract : As the COVID-19 pandemic began, the residents from our ambulatory clinics were pulled to cover the increasing numbers of hospitalised patients. To provide care for our 40 000 patients, without resident support, we needed to develop quickly a new culture of communication and innovation. We accomplished this by regular, transparent meetings with senior leadership and key stakeholders who were empowered to make rapid decisions. We then convened regular meetings with clinic leadership and frontline providers to receive feedback and implement new practices. These rapid meeting cycles allowed for a nimble response to a changing landscape. We optimised our video-conferencing and telehealth services, reached out to our most vulnerable patients and engaged other providers and medical students who were not engaged in patient care due to social isolation practices. We discuss the implications of these innovations on our future practice.